use identity to find the product ( x+3) (x-3)
Answers
Answered by
29
☆Hello friend☆
(x+3)(x-3)
![(a + b)(a - b) = {a}^{2} - {b}^{2} \\ (x + 3)(x - 3) = {x}^{2} - {3}^{2} (a + b)(a - b) = {a}^{2} - {b}^{2} \\ (x + 3)(x - 3) = {x}^{2} - {3}^{2}](https://tex.z-dn.net/?f=%28a+%2B+b%29%28a+-+b%29+%3D++%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%5C%5C+%28x+%2B+3%29%28x+-+3%29+%3D++%7Bx%7D%5E%7B2%7D++-++%7B3%7D%5E%7B2%7D+)
x^2- 9
Hope it helps
☺☺☺
_____________________
(x+3)(x-3)
x^2- 9
Hope it helps
☺☺☺
_____________________
Answered by
6
Answer:
(x+3)(x-3)
\begin{gathered}(a + b)(a - b) = {a}^{2} - {b}^{2} \\ (x + 3)(x - 3) = {x}^{2} - {3}^{2}\end{gathered}
(a+b)(a−b)=a
2
−b
2
(x+3)(x−3)=x
2
−3
2
x^2- 9
Similar questions